Penggunaan Metode Profile Matching Untuk Pemilihan Karyawan Berprestasi Pada PT. ARMY Jakarta - Sopiyan Dalis; Syamsul Bahri; Ardhianto Budi Prasetyo (JAIS - Journal of Accounting Information System, 2022)
During the selection process for outstanding employees at PT. There are still many ARMYs in hardcopy and decisions from one side, so the process is still not accurate. The selection of outstanding employees is still done manually so that the search process for selecting outstanding employees is still not effective and often has difficulty in making decisions and finding hardcopy data. From the research conducted, there are several criteria used in making these decisions. The assessment criteria are Discipline Aspects, Cooperation Aspects, Job Performance Aspects, and Work Results Aspects. For this reason, the decision support system is very helpful for companies in terms of making decisions, then analyzed using the Profile Matching method. With the Profile Matching method at PT. ARMY Jakarta makes it easier to make decisions in selecting outstanding employees according to their abilities. This study is to determine the ranking and value weights in the selection of outstanding employees at PT. ARMY Jakarta.